Production of Biosorbents from Citrus Wastes for Adsorption of Pollutants and Salt from Wastewaters - Farbod Papoli Yazdi; Saeed Reza Khodashenas; Mohamad Talati (آب و توسعه پایدار)
Water and wastewater companies must conduct risk assessments and develop management plans to mitigate risks and enhance resilience. This process involves identifying vulnerable assets, associated threats, and the potential consequences for the company and society. Financially justified countermeasures are then proposed to reduce risk and increase resilience. The result of the risk assessment is the development of a risk management plan model. Climate change has significantly impacted water supply systems, particularly in countries like Iran. By monetizing risk impacts, and comparing costs of current risks with those under managed adaptation programs, the operational resilience of a water supply system can be determined. This research examines the current resilience of the JVWCD facility, which serves 220,000 people, using the US Environmental Protection Agency's Climate Resilience Assessment Tool (CREAT). Climate projections for the region were made for 2060 and 2070. Assets and threats were identified, and their financial risks were assessed. Feasible long-term adaptation scenarios were extracted from the CREAT library, and two models, GWM and AIMD-P, were evaluated as adaptation plans until 2060. The evaluations indicated that implementing the GWM model would increase resilience by 68 percent compared to the current situation. If both models are implemented, resilience will increase to 92 percent of the current level, resulting in a financial optimization of 93 million dollars.